The Care Bears' party cookbook - O'Connor, Jane; Sustendal, Pat (New York : Random House, 1985)
Presents simple cooking principles and easy recipes for a variety of party dishes including cakes, shakes, and ice cream.
Keywords: Cooking -- Juvenile literature